Penerapan Model Pembelajaran Missouri Mathematics Project (MMP) dalam Menarik Minat Belajar Matematika Siswa - Lukluil Maknun (JUMAT: Jurnal Matematika, 2025)
Students’ low interest in mathematics is an instructional problem because mathematics is often perceived as difficult and less engaging. This study describes the implementation of the Missouri Mathematics Project (MMP) learning model in attracting students’ interest in learning mathematics in class VII-B of SMP Negeri 9 Pasuruan. The study used a descriptive quantitative approach and was conducted in the odd semester of the 2023/2024 academic year. The subjects were 30 students, consisting of 15 female and 15 male students. The learning process followed the MMP stages: review, concept development, controlled practice, seatwork, and assignment. The instrument was a 24-item mathematics learning interest questionnaire covering enjoyment, attention, interest, and involvement. The data were analyzed using a percentage formula and classified according to learning interest criteria. The results showed that enjoyment reached 74.44%, attention 75.41%, interest 77.22%, and involvement 72.36%. Overall, students’ mathematics learning interest reached 74.86%, categorized as fair. Therefore, MMP can attract students’ interest in learning mathematics, particularly in the interest aspect.